2010
DOI: 10.1088/0022-3727/43/38/385202
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of collisional quenching rate of nitrogen states N2(C 3Πu, v = 0) and

Abstract: This paper presents an experimental investigation of the effect of the electric field strength on the collisional quenching rate of nitrogen states N 2 (C 3 Π u , v = 0) and N 2 + (B 2 Σ + g , v = 0) by nitrogen and oxygen molecules. In experiments, the pulses of non-self-sustained electrical discharge excite gas molecules. The range of reduced electric field strength is from 240 to 4000 Td at pressure range from 70 to 4300 Pa. The experiments show that the field strength has no effect on the quenching rate. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 60 publications
3
58
0
Order By: Relevance
“…The lifetime of N 2 (C,0) state is determined by the radiative decay and by quenching in collisions with the host gas particles and electrons. Radiative decay frequency of N 2 (C,0) state is ca s -1 [23]. (4) 70% of OH(A) is produced in the vibrational state v=0, ca 25% -in the state v=1 and 5% -in the state v=2.…”
Section: Determination Of Rotational Temperaturementioning
confidence: 99%
“…The lifetime of N 2 (C,0) state is determined by the radiative decay and by quenching in collisions with the host gas particles and electrons. Radiative decay frequency of N 2 (C,0) state is ca s -1 [23]. (4) 70% of OH(A) is produced in the vibrational state v=0, ca 25% -in the state v=1 and 5% -in the state v=2.…”
Section: Determination Of Rotational Temperaturementioning
confidence: 99%
“…35 The other loss mechanisms can usually be neglected. The most important excitation processes for the N 2 (C 3 P u ) state are electron excitation from the ground state N 2 (X 1 R g þ ) (10), 38 Penning excitation by argon metastable atoms Ar( 3 P 2 ) (11) (Ref.…”
Section: B Argon Metastable Lifetimesmentioning
confidence: 99%
“…[35][36][37][38] The excitation coefficients for reaction (10) and for reactions (11) and (12) are well known. Based on the measured argon metastable density n m Ar ¼ (0.1-2.5)10 10 cm À3 and the previously estimated electron density n e ¼ 2 Â 10 10 cm À3 , it can be shown that reaction (11) can be neglected by comparing to Eq.…”
Section: B Argon Metastable Lifetimesmentioning
confidence: 99%
“…All rate constants as well as the lifetimes τ 0 of the excited states were taken from [48] except for k B conv , which was taken from [44]. All rate constants as well as the lifetimes τ 0 of the excited states were taken from [48] except for k B conv , which was taken from [44].…”
Section: Gas Temperature and Reduced Electric Fieldmentioning
confidence: 99%